A descriptive analysis of anglicisms used in Ecuadorian Magazines - Salvador Valle, Pablo Francisco (2011)
The bibliographic method was an important part as method to collect available information about this topic; thus the bibliographic information was gathering by note-taking technique and instruments such as bibliographic cards. To develop the investigation the descriptive and analytical methods were used; consequently, the investigation contains the linguistic and comparative analysis. The first one covers three aspects such as: morphological, semantic and syntactic analysis and the second one was done with the anglicisms found in each variable and later they were compared among the variables.